If f(x)= 2x 2 + 3, then f(x - 1)= 2x 2 + 4x + 5. true or false

Question

Asked 5/2/2012 8:31:53 AM

Updated 1/17/2014 5:40:02 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [1/17/2014 5:37:20 AM]

s

BhawikJain|Points 316|

Expert answered|coolcatrina|Points 293|

Question

Asked 5/2/2012 8:31:53 AM

Updated 1/17/2014 5:40:02 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [1/17/2014 5:37:20 AM]

Rating

8

10 + 4(3 + 2) + 5 + (12 ÷ 6)

10 + 4(5) + 5 + 2

10 + 20 + 5 + 2

30 + 7

= 37

10 + 4(5) + 5 + 2

10 + 20 + 5 + 2

30 + 7

= 37

Added 1/17/2014 5:37:18 AM

This answer has been confirmed as correct and helpful.

8

[3(5 + 6) + 2] ÷ 7

[3(11) + 2] ÷ 7

[33 + 2] ÷ 7

35 ÷ 7

= 5

[3(11) + 2] ÷ 7

[33 + 2] ÷ 7

35 ÷ 7

= 5

Added 1/17/2014 5:39:21 AM

This answer has been confirmed as correct and helpful.

8

9/11 + 3/4

= 69/44 or 1 25/44

= 69/44 or 1 25/44

Added 1/17/2014 5:40:02 AM

This answer has been confirmed as correct and helpful.

33,810,441

questions answered

There are no comments.